2004
DOI: 10.1023/b:bmmd.0000048562.29657.64
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Chemotherapy Simulations Demonstrate Fundamental Transport and Tumor Response Limitations Involving Nanoparticles

Abstract: Zheng et al. (2004) developed a multiscale, two-dimensional tumor simulator with the capability of showing tumoral lesion progression through the stages of diffusion-limited dormancy, neo-vascularization (angiogenesis) and consequent rapid growth and tissue invasion. In this paper we extend their simulator to describe delivery of chemotherapeutic drugs to a highly perfused tumoral lesion and the tumor cells' response to the therapy. We perform 2-D simulations based on a self-consistent parameter estimation tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 29 publications
3
89
0
Order By: Relevance
“…Consequently, our results support the contention of Cristini et al (2005) that treatments that seek to normalize the tumor vasculature (by selectively "pruning" weak blood vessels with targeted anti-angiogenic therapy) may stabilize the tumor morphology by providing the tumor with increased access to nutrient. Since such treatments may also increase the accessibility of the tumors to chemotherapeutic agents (Jain, 2001;Sinek et al, 2004), our results provide additional support for the use of targeted anti-angiogenic therapy as an adjuvant therapy to chemotherapy and resection. This is currently under investigation.…”
Section: Discussion and Future Workmentioning
confidence: 52%
See 1 more Smart Citation
“…Consequently, our results support the contention of Cristini et al (2005) that treatments that seek to normalize the tumor vasculature (by selectively "pruning" weak blood vessels with targeted anti-angiogenic therapy) may stabilize the tumor morphology by providing the tumor with increased access to nutrient. Since such treatments may also increase the accessibility of the tumors to chemotherapeutic agents (Jain, 2001;Sinek et al, 2004), our results provide additional support for the use of targeted anti-angiogenic therapy as an adjuvant therapy to chemotherapy and resection. This is currently under investigation.…”
Section: Discussion and Future Workmentioning
confidence: 52%
“…hypoxic) conditions may lead to instability. Zheng et al did not fully investigate the interaction between the growth progression and the tumor microenvironment, but their work served as a building block for recent studies of the effect of chemotherapy on tumor growth by Sinek et al (2004) and for studies of morphological instability and invasion by Cristini et al (2005) and Frieboes et al (2006b). Hogea et al (2006) have also begun investigating tumor growth and angiogenesis using a level set method coupled with a continuous model of angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…These results support the contention [55] that treatments that seek to normalize tumor vasculature (by selectively "pruning" weak blood vessels with targeted anti-angiogenic therapy) may stabilize tumor morphology by providing increased access to nutrient. Since such treatments may also increase the accessibility to chemotherapeutic agents [105,188], our results provide additional support for the use of targeted anti-angiogenic therapy as adjuvant to chemotherapy and resection.…”
Section: Discussionmentioning
confidence: 53%
“…As in [59], Zheng et al found that low-nutrient (e.g., hypoxic) conditions could lead to morphological instability. Their work served as a building block for recent studies of the effect of chemotherapy on tumor growth by Sinek et al (2004) [188] and for studies of morphological instability and invasion by Cristini et al, (2005) [55] and Frieboes et al (2006) [74]. Hogea et al (2006) [97] have also begun exploring tumor growth and angiogenesis using a level set method coupled with a continuum model of angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Using a continuum approach, Cristini and co-workers have established a series of exploratory investigations on mathematical analysis of morphologic stability in growth and invasion of highly malignant gliomas [17,18,25,26,53,56,73]. They propose that tumor tissue dynamics can be simply regulated by two dimensionless parameters: one quantifies the competition between local cell proliferation (contributing to tumor mass growth) and cell adhesion (which tends to minimize the tumor surface area), while the other one represents tumor mass reduction related to cell death.…”
Section: Continuum Modelingmentioning
confidence: 99%